Playing with Lego: constructing modular interactive digital learning resources - Silva, P (Students, Transitions, Achievement, Retention & Success (STARS), 2015)
The development of innovative digital interactive learning resources to develop academic literacies has been a key driver of the Auckland University of Technology Student Learning Centre. This pilot project derived from both a student and staff identified gap. Thus, the Student Learning Centre decided to support the development of staff lead research that would contribute to the identification, discussion and proposal of new and innovative approaches to support students in this area. This paper outlines a pilot project to create a series of digital, modular and interactive learning resources aimed at developing academic literacies. The presentation of this new idea at a conference will allow a valuable opportunity to collect feedback before the project is implemented.